Analisis Determinan Loyalitas Nasabah Bank Syariah Indonesia Kantor Cabang Pembantu Kendal Weleri - Anggi Nadia Nurohmah; Agung Guritno (IAIN Batusangkar, 2023)
This study aims to analyze the effect of Marketing Communication, Excellent Service and Emotional Branding on Customer Loyalty with Satisfaction as an Intervening Variable. This study uses a quantitative descriptive approach with primary data obtained through distributing questionnaires. The results showed that Marketing Communication had a positive and insignificant effect on Loyalty and Satisfaction while Excellent Service had a negative and insignificant effect on Loyalty but had a positive and insignificant effect on satisfaction. Only Emotional Branding has a direct significant positive effect on Loyalty. Satisfaction has a significant positive effect on Loyalty. Satisfaction is unable to mediate the effect of Marketing Communication and Emotional Branding on Loyalty, and Satisfaction is able to mediate the effect of Excellent Service on Loyalty.